ANALYSIS THE PERFORMANCE OF SHARIA AND CONVENTIONAL EQUITY MUTUAL FUNDS (STUDY FOR BIBIT APPLICATION DURING JANUARY 2022-JUNE 2025) - Risma Nada Insyiroh; Yuni Astuti (JURNAL PROFIT, 2026)
This study aims to analyze the difference in performance between sharia stock mutual funds and conventional stock mutual funds available on the Bibit application during the period from January 2022 to June 2025. This study uses a quantitative approach with secondary data in the form of monthly Net Asset Value (NAV). The research sample amounted to 35 mutual funds, consisting of 8 sharia stock mutual funds and 27 conventional stock mutual funds, which were selected using purposive sampling techniques based on criteria that had been set according to the research objectives. Performance measurement was carried out using the Sharpe Ratio, Treynor Ratio, Jensen Alpha, M², Information Ratio, RMAR, and RDIV methods. Furthermore, differential testing was performed with the Independent Sample T-Test for normally distributed data and the Mann-Whitney U Test for non-normally distributed data. The results of the study show that there are significant differences in the Sharpe Ratio, RMAR, and Jensen Alpha indicators, while in the Treynor Ratio, M², Information Ratio, and RDIV indicators, no significant differences were found between the two types of mutual funds. Conventional stock mutual funds show better performance based on the Sharpe Ratio and RMAR indicators, while Islamic equity mutual funds are superior to the Jensen Alpha indicator. Overall, the results of the study show that conventional stock mutual funds tend to have better performance than Islamic stock mutual funds during the study period.